2011
DOI: 10.1590/s1677-55382011000200010
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of penile cancer in Rio de Janeiro: evaluation of 230 cases

Abstract: Purpose: To determine epidemiological characteristics of penile cancer in Rio de Janeiro, its associated risk factors and clinical manifestations. Patients and Methods: Between 2002 and 2008 we evaluated 230 patients at three public institutions, considering age, ethnicity, birthplace, marital status, educational level, religion, tobacco smoking, presence of phimosis and practice of circumcision. Results: The ages ranged from 25 to 98 years, with an average of 58.35 years. Of the 230 patients, 167 (72.7%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
4
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 35 publications
3
50
4
12
Order By: Relevance
“…The average age of the patients at diagnosis predominates in advanced age (>50 years), which suggests that men seek health services very late in life [15]. Younger individuals are also affected, but in smaller percentages [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average age of the patients at diagnosis predominates in advanced age (>50 years), which suggests that men seek health services very late in life [15]. Younger individuals are also affected, but in smaller percentages [7].…”
Section: Resultsmentioning
confidence: 99%
“…Koifman et al [15] reported the presence of invasion of the spongiosum or cavernous corpus in 41.3% of the patients.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have confirmed a predominance of penile cancer in the North and Northeast of Brazil which are regions with lower human development indexes (Favorito et al, 2008;Koifman et al, 2011;Reis et al, 2010a). Scheiner et al (2008) in Rio de Janeiro, Brazil found that HPV infection may have contributed to malignant transformation in a large proportion of their penile cancer cases but only inguinal metastasis was a prognostic factor impacting survival of those patients.…”
Section: Wwwintechopencommentioning
confidence: 95%
“…Koifman (2011) reported that penile cancer was more prevalent in patients born in the state of Rio de Janeiro. According to the data from the Brazilian Ministry of Health, there is an estimated 850 partial or complete penile surgical procedures performed in the context of malignancy yearly within Brazil, with approximately 50% of these procedures being performed in the North and Northeast regions of the country (Favorito et al, 2008).…”
Section: Epidemiology and Natural History Of Penile Cancermentioning
confidence: 99%
“…In a case control study in Denmark, of the 37 penile SCC patients whose tumor tissues were PCRexamined for the presence of HPV DNA, 24 (65%) were high-risk HPV positive, and 1 (3%) was positive to a low-risk HPV type (HPV 6) [Madsen et al, 2008]. Several studies have confirmed a predominance of penile cancer in the North and Northeast of Brazil which are regions with lower human development indexes (Favorito et al, 2008;Koifman et al, 2011;Reis et al, 2010a). Scheiner et al (2008) in Rio de Janeiro, Brazil found that HPV infection may have contributed to malignant transformation in a large proportion of their penile cancer cases but only inguinal metastasis was a prognostic factor impacting survival of those patients.…”
Section: Effect On the Sperm Parametersmentioning
confidence: 99%